Use of copyrighted objects in advertising in the context of problems of exclusive rights exhaustion - Євков, Андрій Миколайович (Problems of legality, 2016)
The article examines issues of legal regulation of copyrighted works’ civil circulation in the scope of usage of copyrighted works in order to advertise goods containing such works after their first legitimate sale. These issues are described in close connection with the problem of use of so-called principle of exhaustion of exclusive intellectual property rights, also known as first-sale doctrine. The article analyzed the set of author’s exclusive powers which are used in the process of advertising of goods containing protected works. It also examines whether such author’s exclusive powers are exhausted after first legitimate purchase of such goods and what criteria must be met in this regard. The article focuses on the fact that the solution of abovementioned question depends on identification of the exclusive rights purpose, so-called specific subject matter of exclusive rights, and also on strict observance of private and public interests balance. In the paper there also described relevant examples of court practice, especially the EU court decisions, which are important for the correct interpretation of legislation.